Performance determinants and evidence-based practice in track cycling: a survey of coaches, practitioners, and athletes - Stadnyk, A. M. J.; Impellizzeri, F. M.; Stanley, J.; Menaspà, P.; Slattery, K. M. (Journal of Science and Medicine in Sport, 2024)
Objectives This study examined how track cycling coaches, practitioners, and athletes: develop knowledge and practices; value performance areas; and, implement research into practice.